Do Natural Disasters Affect the Poor Disproportionately? Price Change and Welfare Impact in the Aftermath of Typhoon Milenyo in the Rural Philippines. (June 2017) - Sakai, Yoko; Estudillo, Jonna P.; Fuwa, Nobuhiko; Higuchi, Yuki; Sawada, Yasuyuki
Summary: This paper illustrates the sharp contrast in welfare impacts between the rich and the poor caused by typhoon Milenyo in a Philippine village. We find that fish prices dropped sharply due to the damage caused to fish pens near the village, leading to positive net welfare gains among the wealthy. In contrast, the poor do not consume much fish and thus did not gain from the sharp decline in prices. Finally, consumption reallocation played an important role as an ex post risk-coping measure, albeit only among the wealthy, who are relatively well-protected against typhoons.